Comparing responses to violence and uncertainty in Brazil and the UK: a collaborative project - Cameron (The Open University, UK), Lynne (ANTARES: Letras e Humanidades, 2012)
This article situates a collaborative project between Brazil and the UK that aims to compare people's responses to violence in the two contexts through a report of the method and findings of the original UK study. The Perception and Communication of Terrorist Risk project investigated responses to terrorist risk by focus groups of Muslims and non-Muslims in London and Leeds, some months after the London bombings of July 2005, which were carried out by young Muslim men. Metaphor-led discourse analysis revealed people's feelings of fear, and their use of metaphors to talk about: the impact of terrorism, the actions of terrorists, the effect on British Muslims, how the media and authorities responded to the attacks, and the social landscape. The Brazil study will compare these findings with Brazilian focus group responses to urban violence in two cities. I reflect on how the collaborating team has addressed methodological challenges of working bilingually and look forward to the emerging findings.